Answer:
x²+ y² - 109 = 0
Explanation:
The coordinate of centre of circle = (-6 , 6)
Point through which it passes = (3 , -4)
So , Firstly find the distance between the centre and that point that will be equal to the radius . Using Distance Formula we have ,
⇒ D = √ [ ( x - x' )² + ( y + y')² ]
⇒ D = √ [ (3+6)² + (6+4)² ]
⇒ D = √ [ 9² + 10² ]
⇒ D = √ [ 81 + 100 ]
⇒ D = √ 181
⇒ D = 13.45 .
Now substituting the respective values in the general equation of circle .
⇒ ( x - h)² + (y - k)² = r²
- Where (h,k) is the centre and r is the radius.
⇒ { x - (-6) }² + { y - (6) }² = (13.45)²
⇒ ( x + 6 )² + ( y - 6)² = 13.45²
⇒ x² + 36 + 12x + y² + 36 -12x = 181
⇒ x² + y² + 72 = 181
⇒ x² + y² + 72 - 181 = 0
⇒ x² + y² - 109 = 0
Therefore the equation of the circle is x² + y² - 109 = 0 .